Effects of eccentric-overload vs. free-weight high load resistance training on throwing velocity in elite young male handball players - Larrumbide, P.; Daza, G.; Toro-Román, V.; Font, R.; Cadens, M.; Fernández-Valdés, B. (Sports, 2026)
Throwing velocity is a key performance factor in handball and may be enhanced through strength training. The aim of the present study was to quantify improvements in throwing velocity in handball players and to compare the effects of a free-weight strength training programme (FW; n = 14; 18.07 ± 1.27 years; 86.19 ± 9.67 kg; 1.85 ± 0.08 m) and a flywheel-based eccentric overload training programme (FLYW; n = 13; 17.77 ± 1.17 years; 85.5 ± 8.38 kg; 1.85 ± 0.06 m). A total of 27 elite male youth handball players (n = 27; 17.93 ± 1.21 years; 85.86 ± 8.90 kg; 1.85 ± 0.07 m) participated in the study. Participants were allocated to groups using a stratified randomisation approach based on team and playing position. Of these, 14 performed the FW training program and 13 completed the FLYW training protocol. The FW group performed 3 sets of 6 repetitions at 80% of 1RM, with 3 min of rest between sets, using the exercises half squats, bench presses and pullovers. The FLYW training group trained with flywheel devices, executing 3 sets of 6 repetitions using four inertial loads, performing each repetition at maximal intended velocity, with 3 min of rest between sets, using the exercises unilateral press, overhead elbow extension, and trunk rotation. Both groups trained twice per week for 8 weeks, in combination with regular handball-specific training. Pre- and post-intervention assessments included the indirect estimation of one-repetition maximum (1RM) in the half squats, bench presses, and pullovers, as well as throwing velocity. The FW group showed significant improvements in all variables (bench press, half squat, pullover, and throwing velocity; all p < 0.05). In contrast, the FLYW group showed significant improvements only in half squats (p = 0.034) and throwing velocity (p = 0.008). An 8-week strength training program using free weights and flywheel methods improved throwing velocity in elite youth handball players; however, neither method demonstrates clear superiority when throwing velocity is the primary outcome.